Destins De Femmes : French Women Writers, 1750-1850 - John Claiborne Isbell (Open Book Publishers, 2023)
Destins de femmes is the first comprehensive overview of French women writers during the turbulent period of 1750-1850. John Isbell provides an essential collection that illuminates the impact women writers had on French literature and politics during a time marked by three revolutions, the influx of Romantic art, and rapid technological change. Each of the book's thirty chapters introduces a prominent work by a different female author writing in French during the period, from Germaine de Staël to George Sand, from the admired salon libertine Marie du Deffand to Flora Tristan, tireless campaigner for socialism and women's rights. Isbell draws from multi-genre writers working in prose, poetry and correspondence and addresses the breadth of women's contribution to the literature of the age. Isbell also details the important events which shaped the writers'lives and contextualises their work amidst the liberties both given and taken away from women during the period. This anthology fills a significant gap in the secondary literature on this transformative century, which often overlooks women who were working and active. It invites a further gendered investigation of the impact of revolution and Romanticism on the content and nature of French women's writing, and will therefore be appropriate for both general readers, students, and academics analysing history and literature through a feminist lens.